Clinicians' recognition and management of emotions during difficult healthcare conversations. Issue 10 (October 2015) - Martin, Elliott B.; Mazzola, Natalia M.; Brandano, Jessica; Luff, Donna; Zurakowski, David; Meyer, Elaine C.
Abstract Objective To examine the most commonly reported emotions encountered among healthcare practitioners when holding difficult conversations, including frequency and impact on care delivery. Methods Interprofessional learners from a range of experience levels and specialties completed self-report questionnaires prior to simulation-based communication workshops. Clinicians were asked to describe up to three emotions they experienced when having difficult healthcare conversations; subsequent questions used Likert-scales to measure frequency of each emotion, and whether care was affected. Results 152 participants completed questionnaires, including physicians, nurses, and psychosocial professionals. Most commonly reported emotions were anxiety, sadness, empathy, frustration, and insecurity. There were significant differences in how clinicians perceived these different emotions affecting care. Empathy and anxiety were emotions perceived to influence care more than sadness, frustration, and insecurity. Conclusions Most clinicians, regardless of clinical experience and discipline, find their emotional state influences the quality of their care delivery. Most clinicians rate themselves as somewhat to quite capable of recognizing and managing their emotions, acknowledging significant room to grow. Practice implications Further education designed to increase clinicians' recognition of, reflection on, and management of emotion would likely prove helpful in improving their ability to navigate difficult healthcare conversations. Interventions aimed at anxiety management are particularly needed.